EKSPLORASI BIBLIOMETRIK BERDASARKAN DATA SCOPUS (2013-2023): HUBUNGAN ANTARA MODERATE EXERCISE DAN SIKLUS MENSTRUASI TERATUR PADA REMAJA - Perestroika, Grhasta Dian; Argaheni, Niken Bayu; Prastika, Dewi Andang; Syarifah, Syarifah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
By conducting a bibliometric analysis based on Scopus data from 2013 to 2023, this study provide a comprehensive overview of the research landscape concerning the interaction between moderate exercise and regular menstrual cycles in adolescents. This study aims to inform researchers, educators, clinicians, and policymakers about existing knowledge, identify research gaps, and guide future investigations. The Scopus database was utilized for data collection and analysis. The keywords used for the search included